Discourse on the Substance and Existence of Evangelism According to Literary Descriptions - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2024)
Evangelism is at the core of the Christian mission, which has been a subject of profound study in religious literature. This article discusses the complexity of evangelism service across time, culture, generations, organizations, and sectors. In an academic context, qualitative research methods with content analysis are employed to explore the substance and existence of evangelism. Through the selection of relevant literature and careful content analysis, this article successfully reveals patterns, themes, and essential understandings related to evangelism. The conclusion of this research emphasizes the importance of the role of the Holy Spirit in evangelism, as well as the involvement of individuals and churches in ministry, and then how relevant it is to the context of theology and church practice. This article is expected to make a significant contribution to the development of relevant and impactful thinking and practices of evangelism, while offering a deeper understanding of the role of evangelism in the mission of the church in the modern era.